A Clinical Study for the Development of a Bee Venom Allergy Diagnostic Kit - Jun-Sang Yu; Min-Jeong Kim; Chang-Woo Seon; Hee-Jun Na; Jae-Wan Jung; Yun-Suk Lee (Journal of Pharmacopuncture)
Objectives: In South Korea, bee venom pharmacopuncture (BVP) is used for various conditions, such as pain, neurodegenerative diseases, and cancer. However, there is a risk of side effects. To determine whether there are systemic allergic side effects of BVP, we compared the total IgE level before and after BVP injection with skin test results as a fundamental study for the safe use of BVP. Methods: Thirty volunteers, who were informed about the study, agreed to participate; one had an adverse reaction to the skin test. Blood was collected before and after injecting 0.3 cc of 10% (1 mg/mL) bee venom (melittin) for joint pain, and the corresponding total IgE levels were measured for comparison. Results: The total IgE level did not significantly change one hour after BVP injection. Ten subjects had an IgE level greater than the threshold of 100 kU/L, while 19 had an IgE level < 100 kU/L. Total IgE and wheal size were partially correlated. Moreover, the correlation coefficients between total IgE and the Mada Total IgE kit were as high as r = 0.99 in plasma, and r = 0.98 in blood. Conclusion: To develop a Venom Allergy Diagnostic Kit for the safe use of BVP therapy, we compared the wheal size and redness size from a skin test, before and after BVP injection. In addition, the correlations between total IgE level and the Mada total IgE kit level in plasma and blood were significantly high, indicating that measuring the total IgE level in blood might be clinically valid. In the future, it is necessary to develop a diagnostic device that can detect melittin antibodies to determine the presence of systemic allergic reactions.